Marrying Daisy Bellamy - Wiggs, Susan (Don Mills, Ont. : MIRA, 2011)
Daisy Bellamy has struggled for years to choose between two men -- one honorable and steady, one wild and untethered. And then, one fateful day, the decision is made for her.
Keywords: Women photographers -- Fiction; Prisoners of war -- Fiction; Love stories